PENYULUHAN HUKUM BAHAYA NARKOBA BAGI GENERASI MUDA PADA MASYARAKAT KEBONAGUNG KECAMATAN PLOSO JOMBANG - Arkisman, Arkisman; Ningsih, Dwi Wachidiyah; Nasichin, Moh (Universitas Muhammadiyah Gresik, 2023)
The abuse of narcotics and illegal drugs among the younger generation is currently increasing, and deviant behavior among the younger generation can threaten the survival of this nation in the future. Narcotics Law No. 35 of 2009 regulates investigation, prosecution and preliminary examination in narcotics criminal court sessions, more precisely in §§ 73-103. In each line of drug cases, the investigation process is the most important process in eradicating drug dependence. Article 35 of Law Number 2009 concerning Narcotics also contains Article 54 which regulates rehabilitation. Article 54, which reads: